O impacto da extensão universitária sobre a formação acadêmica em Odontologia - Fadel, Cristina Berger; Bordin, Danielle [UNESP]; Kuhn, Eunice; Martins, Luciana Dorochenko (Universidade Estadual Paulista (Unesp), 2013)
This qualitative study of descriptive and exploratory nature was conducted with the aim of evaluating the contribution of university extension towards the training and life histories of dentistry students, using the focus group technique. The material was assessed using the collective subject discourse analysis technique. The results showed the impact exerted by academic experience, in extension activities within the personal, professional and active citizenship spheres. The subjects' perceptions revealed an opportunity to develop and improve their professional skills, through recognition of distinct realities of life, through breaking away from the traditional model of teaching and through fruitful relationships between students, university and society. Feelings of satisfaction, personal fulfillment, recognition and being an active and critical citizen were reported. It was concluded that experience within the field of extension is an important agent for the individual and collective process of academic training.

Com objetivo de avaliar a contribuição da extensão universitária na formação e história de vida de estudantes de Odontologia, realizou-se um estudo qualitativo, de caráter descritivo-exploratório, utilizando a técnica do grupo focal. O material foi analisado com a técnica de análise do discurso do sujeito coletivo. Os resultados referiram-se ao impacto exercido pela vivência acadêmica em atividades extensionistas nos campos pessoal, profissional e da cidadania. As percepções dos sujeitos revelaram a oportunidade de desenvolvimento e aprimoramento de suas habilidades profissionais, por meio do reconhecimento de distintas realidades de vida, da ruptura do modelo tradicional de ensino e do profícuo relacionamento entre acadêmico, universidade e sociedade. Foram relatados sentimentos de satisfação, realização pessoal, reconhecimento, e de ser um cidadão ativo e crítico. Conclui-se ser a experiência no campo da extensão um importante agente para o processo individual e coletivo de formação acadêmica.

Se realizó un estudio cualitativo de carácter descriptivo-exploratorio para evaluar la contribución de la extensión universitaria en la formación e historia de vida de los estudiantes de Odontología. Para la recolección de datos fue utilizado el grupo focal y el material fue analizado por medio de la técnica de análisis del discurso del sujeto colectivo. Los resultados se refirieron al impacto ejercido por la vivencia académica en actividades de extensión en los campos personal, profesional y de ciudadanía. Las percepciones de los sujetos revelaron la oportunidad de desarrollo y perfeccionamiento de sus habilidades profesionales, por medio de reconocimiento de distintas realidades de vida, de la ruptura del modelo tradicional de enseñanza y de la provechosa relación entre el sector académico, la universidad y la sociedad. Fueron relatados los sentimientos de satisfacción, realización personal, reconocimiento y de ser un ciudadano activo y critico. Se concluyó que la experiencia en el campo de extensión es un importante agente para el proceso de formación académica individual y colectiva.
El impacto de la extensión universitaria sobre la formación en Odontología
The impact of university extension on academic training in Dentistry
Keywords: Educação Superior; Formação em Odontologia; Grupo focal; Relações comunidade-instituição; Higher education; Dentistry training; Focus group; Community-institution relationships